Wave interaction with defects in pressurised composite structures - Apalowo, R.K.; Chronopoulos, D.; Tanner, G. (Springer, 2018)
There exists a great variety of structural failure modes which must be frequently inspected to ensure continuous structural integrity of composite structures. This work presents a Finite Element (FE) based method for calculating wave interaction with damage within structures of arbitrary layering and geometric complexity. The principal novelty is the investigation of pre-stress effect on wave propagation and scattering in layered structures. A Wave Finite Element (WFE) method, which combines FE analysis with periodic structure theory (PST), is used to predict the wave propagation properties along periodic waveguides of the structural system. This is then coupled to the full FE model of a coupling joint within which structural damage is modelled, in order to quantify wave interaction coeffcients through the joint. Pre-stress impact is quantified by comparison of results under pressurised and non-pressurised scenarios. The results show that including these pressurisation effects in calculations is essential. This is of specific relevance to aircraft structures being intensely pressurised while on air. Numerical case studies are exhibited for different forms of damage type. The exhibited results are validated against available analytical and experimental results.